RESULTS OF THE STUDY OF IMMUNE SYSTEM INDICATORS IN WOMEN WITH INFLAMMATORY DISEASES OF SMALL PELVIS ОRGANS (Conferencea, 2022)
The aim was to analyze its results by studying the indicators of the immune system of women with inflammatory disease of small pelvis members.